2015
DOI: 10.1039/c5ra13846a
|View full text |Cite
|
Sign up to set email alerts
|

Role of Zn-interstitial defect states on d0 ferromagnetism of mechanically milled ZnO nanoparticles

Abstract: An impurity defect level formed by interstitial zinc at the surfaces of undoped ZnO nanoparticles plays a crucial role for d0 ferromagnetism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Thus shifts in the intensity of the E high 2 and E low 2 modes would be consistent with large shifts in the concentrations of O and Zn vacancies and interstitials. Previously, it has been reported that the A 1 (LO) mode is affected by the presence of defects 32 . Hence, Raman studies confirm that the SHI irradiation treatment introduces disorder into the nanostructures, which certainly includes large concentrations of intrinsic point defects associated with the O and Zn sublattices.…”
Section: Resultsmentioning
confidence: 99%
“…Thus shifts in the intensity of the E high 2 and E low 2 modes would be consistent with large shifts in the concentrations of O and Zn vacancies and interstitials. Previously, it has been reported that the A 1 (LO) mode is affected by the presence of defects 32 . Hence, Raman studies confirm that the SHI irradiation treatment introduces disorder into the nanostructures, which certainly includes large concentrations of intrinsic point defects associated with the O and Zn sublattices.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the intrinsic or extrinsic defects are popularly investigated by researchers via simulations or experiments to depress and enhance the useless and useful defects, respectively. Zn i and V O play role as donors in ZnO material [3][4][5]. Ghose et al [4] proved that Zn i and V O can exist in different charged states.…”
Section: Introductionmentioning
confidence: 99%
“…Zn i and V O play role as donors in ZnO material [3][4][5]. Ghose et al [4] proved that Zn i and V O can exist in different charged states. For example, the yellow emission from photoluminescence spectra is attributed to doubly charged oxygen vacancies (V •• O ) ( • is the Kröger-Vink notation) or the blue luminescence is attributed to Zn i .…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, RTFM has been observed in a number of pure low dimensional nanosized metal oxides, such as SnO 2 [4,5], ZnO [6,7], CuO [8,9], MgO [10,11], Al 2 O 3 [5,12], CaO [13], etc. It has been identified that d 0 ferromagnetism is closely related to the existence of defects at the surface regions [14]. These defects may confine the compensating charges in molecular orbitals, forming local magnetic moments, and RTFM may be established only if the defect concentration essentially exceeds that of its equilibrium magnitude [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is now believed that both -the surface non-stoichiometry and the defects of oxide nanostructures play a crucial role in the observance of RTFM, since conventional ideas of magnetism are unable to account for d 0 ferromagnetism [16]. However, the main obstacle to the use such materials for the fabrication of potential devices is the lack of understanding of the role of defects [14]. This somewhat controversial research topic definitely requires further detailed investigations.…”
Section: Introductionmentioning
confidence: 99%